Endogenous L-Carnosine Level in Diabetes Rat Cardiac Muscle. (13th April 2016) - Liu, Yali; Su, Dan; Zhang, Ling; Wei, Shaofeng; Liu, Kuangyi; Peng, Mi; Li, Hanyun; Song, Yonggui
Abstract : A novel method for quantitation of cardiac muscle carnosine levels using HPLC-UV is described. In this simple and reliable method, carnosine from the rat cardiac muscle and the internal standard, thymopentin, were extracted by protein precipitation with acetonitrile. The method was linear up to 60.96 μ g·mL −1 for L-carnosine. The calibration curve was linear in concentration ranges from 0.5 to 60.96 μ g·mL −1 . The relative standard deviations obtained for intra- and interday precision were lower than 12% and the recoveries were higher than 90% for both carnosine and internal standard. We successfully applied this method to the analysis of endogenous carnosine in cardiac muscle of the diabetes rats and healthy control rats. The concentration of carnosine was significantly lower in the diabetes rats group, compared to that in the healthy control rats. These results support the usefulness of this method as a means of quantitating carnosine and illustrate the important role of L-carnosine in cardiac muscle.